PEMANFAATAN ARANG AKTIF CANGKANG BUAH BINTARO (Cerbera manghas) SEBAGAI ADSORBEN PADA PENINGKATAN KUALITAS AIR MINUM - Djeni Hendra; Armi Wulanawati; Kamela Gustina; Heru Wibisono (BRIN Publishing, 2015)
Bintaro seed is widely used as an alternative raw material for biodiesel and waste the fruit-shell. This paper studies the utilization of fruit-shell waste for activated carbon. Activated charcoal was relied on two factors, namely chemical activator (H₃PO₄ concentration) and activation time of hot steam. Activated charcoal quality was tested against Indonesian National Standard (SNI 06-3730-1995). Results show the best activated charcoal is the treatment using H₃PO₄ 15% and 90 minutes hot steam. The process produce activated charcoal quality of 9.98% moisture content, volatile matter 9.16%; ash content 12.45%; fixed carbon 78.4%; adsorption on iodine 784.498 mg/g adsorption on benzene 17.73%; and adsorption on methilene blue 127.705 mg/g. The adsorption mechanism is similar with those adsorption of Langmuir isotherm with linearity of 0.9691. In term of improving water quality the best activated charcoal should be able to reduce the concentration of Fe in the water by 100 % and Mn by 86.94 % respectively.